'Snapchat', youth subjectivities and sexuality: disappearing media and the discourse of youth innocence. Issue 2 (17th February 2018) - Charteris, Jennifer; Gregory, Sue; Masters, Yvonne
ABSTRACT: Research on youth subjectivities and disappearing media is still in its infancy. Ephemeral technologies such as Snapchat, Frankly and Wickr offer young people opportunities for discursive agency, harnessing teenage discourses of social positioning. These media facilitate social mobility in teen peer contexts by providing a medium for dynamic and shifting relationships. The transmission of digital images can enable a social flexibility that has a significant impact on youth subjectivities where discursively constructed relational identities are brokered through cyber technologies. We tackle the question 'what discourses are evoked and produced in the discussion of disappearing social media?' by exploring two parents' accounts of their children's use of this media. We also examine a discourse of innocence that surrounds teens' use of social media and, in particular, ephemeral applications, by sexting and cyberbullying. We engage in the debate on the use of ephemeral social media to consider the discourses influencing youth subjectivities and the nature of networked publics.